Polymorphisms in MCT1, CD147, PDK4, and DMRT3 genes in Arabian and Quarter Horses - Regatieri, Inaê Cristina [UNESP]; Pereira, Guilherme Luis [UNESP]; Teixeira Neto, Antônio Raphael; Ferraz, Guilherme Camargo [UNESP]; Curi, Rogério Abdallah [UNESP]; Queiroz-Neto, Antonio [UNESP] (Elsevier, 2017)
Monocarboxylate transporter isoform 1 (MCT1) and its ancillary protein, CD147 function to transport H+ and lactate ions, retarding systemic acidosis and fatigue. The PDK4 gene is involved in the adenosine triphosphate production, and the DMRT3 gene is involved in the locomotor system. This study investigated polymorphisms of MCT1, CD147, PDK4, and DMRT3 in Arabian and Quarter Horses to associate polymorphisms with performance. Arabian Horses were divided into high performance and untrained horses groups based on success in endurance competition, whereas Quarter Horses were separated by a speed index. Polymorphisms were analyzed by sequencing (MCT1 and CD147), ARMS-PCR (PDK4), and PCR-RFLP (DMRT3). To compare the frequencies of SNPs, the Fisher's exact test was performed in the software R at 5% of significance. The A alleles from the polymorphisms Lys457Gln:1573A>C of MCT1 and Ile51Val:168A>G of CD147 were essentially fixed in both breeds. Only two Arabian from the high performance and one from the untrained horses group appeared AC in MCT1. For the DMRT3 polymorphism (g.22999655C>A:ECA23), all the animals were CC, except one Arabian in the high and two Quarter Horses in the low performance group that were AC. For the PDK4 polymorphism (g.38973231A>G:ECA4), Arabian showed a significantly greater frequency of the G allele than Quarter Horses (P < .01). Considering the kind of exercise practiced by each breed, it is likely that the PDK4 polymorphism influences the pathway to energy production.
Keywords: Fatigue; Lactate; Performance; Sequencing; SNP